The Effect of Development of a Psychoeducation Guidebook in the Management of Postpartum Depression Symptoms: Pengaruh Pengembangan Buku Pedoman Psikoedukasi dalam Penanganan Gejala Depresi Postpartum - Dewi Ningsih; Sakinah Innama (International Journal of Nursing and Health Services (IJNHS), 2021)
Postpartum depression that often occurs after childbirth is a mental health problem related to behavioral and physical health. With the diversity of midwives in providing counseling to postpartum mothers, it is necessary to have a psychoeducation guidebook. The purpose of this research was to determine the effect of the development of a psychoeducation guidebook in the management of postpartum depression symptoms in Banyu Putih Situbondo. This is an R&D research with the mean score of pre-conference and post-conference that increased by 38%. In conclusion, a psychoeducation manual is developed in the handling of symptoms of postpartum depression in the pustu sumberejo region in 2020 as an educational medium for midwives. Pregnant women deserve to be used and can have a good impact when given counseling. Further study needs to measure the family of pregnant women to provide a pleasant postpartum period